Public-Private-Partnerships. Private und staatliche Strategien zum Management von Katastrophenrisiken - Barbara Klimaszewski-Blettner; Andreas Richter (Ludwig-Maximilians-Universität München, Fakultät für Betriebswirtschaft, 2007)
– The continuing trend of increasing frequency and severity of losses from natural and man-made-catastrophes during the last decades has drawn attention to catastrophe risk management. Considering the loss potential of catastrophic events, the private insurance markets' capacity does not seem to be suffi-cient. Problems concerning the supply of adequate catastrophe insurance coverage – resulting mainly from insurability constraints – are aggravated by difficulties of lacking insurance demand. This paper addresses aspects of efficient solutions to increase the supply of and demand for insurance coverage against catastrophic threats. In this context, the government`s role as a risk bearer becomes an increasingly important issue. In particular, we will demonstrate that "pure private" and "pure public" strategies are dominated by "mixed" strategies involving a cooperation of the private and the public sec-tor. Based on an adequate design of a Public-Private Partnership, advantages of the private insurance market can be combined with the state's capacity reserves and power to set a general (legal) framework for improving a society's risk sharing and risk management. Strategies with public involvement are more or less severe interventions in the market system which re-quires them to be well-motivated and makes them applicable under certain conditions only. Supplying public capacity for losses from catastrophe events may be favoured from an economic point of view to expand the limits of insurability, but only by using risk-adequate pricing strategies and not for permanent subsidisation of certain business sectors. The state's role consists not only in supplying coverage capac-ity, but also in setting an adequate general framework (building regulations, land use planning, etc.) to assure necessary claim prevention. On the other hand, in order to increase the demand for catastrophe insurance, establishing mandatory insurance for fundamental risks can be considered as a useful tool for internalizing externalities caused by lacking insurance demand. Besides the introduction of a compulsory insurance system, general conditions must be set by the state in order to assure the acceptance of manda-tory insurance (tax-privileged provisions, public capacity support for "uninsurable" individual risks, etc.).
urn:nbn:de:bvb:19-epub-2026-6
Keywords: G22; G32; 650; Katastrophenrisiken; Versicherungspflicht; Public-Private-Partnership